Can AI Monitor Mental Health Through Smartphone Data? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The proliferation of smartphones and the rapid advancements in artificial intelligence (AI) have opened up new frontiers in healthcare, particularly in the r...
Keywords: AI in Mental Health; Monitor; Mental; Health; Artificial Intelligence; Machine Learning; Healthcare